Studi Eksploratif Pandangan Imam Malik tentang Teori Masalahat dalam Hukum Islam - Rizal Darwis (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This article examines the thoughts of Imam Malik on the masalahat problems in Islamic law. In using al-mashlahat al-mursalah, Imam Malik genuienly provided three limitations or conditions, namely: the existence of a match between the concerns that are considered with maqashid al-shari'ah; the mashlahat relates to matters which are ma'qulat (rational) which according to syara are based on the maintenance of the mashlahat; and the results of al-mashlahat al-mursalah are returned to the maintenance of the dzharuriy (primary) case according to syara and negate the narrowness in religion. The laws contained in Islamic law are oriented towards maintaining the benefit of the mukallaf and rejecting obedience, in order to realize a harmonious life that brings peace and happiness to humans.